Prehabilitation: a narrative review focused on exercise therapy for the prevention of postoperative pulmonary complications following lung resection - Bingül, Emre Sertaç; Şentürk, Nüzhet Mert; Kaynar, Ata Murat (Frontiers in Medicine, 2023)
Extensive preventive strategies in the perioperative period are popular worldwide. Novel “prehabilitation” approaches are being defined for every individual surgical discipline. With intention to reduce perioperative morbidity, “prehabilitation” was developed to increase “physical wellness” considering exercise capacity, nutritional status, and psychological support. Thus, prehabilitation could be well-suited for patients undergoing lung cancer surgery. Theoretically, improving physical condition may increase the chances of having a better post-operative course, especially among frail patients. In this review, we describe the concept of prehabilitation with possible benefits, its role in the Enhanced Recovery After Surgery protocols, and its potential for the future.